The relationship of academic leadership with the organizational confidence of kindergarten teachers - Teacher Dr. Ikram Kadhim Hady (مجلة الدراسات الاقتصادية والادارية, 2022)
The research aims to test the relationship between academic leadership as an independent variable and organizational trust as a dependent variable. Thus, it was necessary to answer a basic question: Is there a correlation and impact relationship between the dimensions of academic leadership and organizational trust? In order to verify the contents of the answer, a sample of governmental kindergarten teachers affiliated to the General Directorate of Education in Baghdad / Karkh1 was chosen and based on the importance of the research topic, and the importance of the research sample and the organization in question. The number of (240) female teachers, representing the research sample out of the total community of (376) female teachers, by adopting the questionnaire as a main tool in data collection, which included (35) paragraphs, as (245) forms were distributed and (240) forms were retrieved, of which were valid For statistical analysis, which was analyzed by adopting the statistical program (Spss V.21, Amos V.18) with the appropriate statistical methods for research, including (frequency distribution, arithmetic mean, coefficient of determination (R²), confirmatory factor analysis and others) to test its hypotheses, and the study found To a set of conclusions, the most important of which is the existence of a direct correlation and impact relationship between the dimensions of academic leadership and organizational trust.